Antiemetic effects of baclofen in a shrew model of postoperative nausea and vomiting: Whole‐transcriptome analysis in the nucleus of the solitary tract. (3rd March 2022) - Konno, Daisuke; Sugino, Shigekazu; Shibata, Tomoko F; Misawa, Kazuharu; Imamura‐Kawasawa, Yuka; Suzuki, Jun; Kido, Kanta; Nagasaki, Masao; Yamauchi, Masanori
Abstract: Aims: The molecular genetic mechanisms underlying postoperative nausea and vomiting (PONV) in the brain have not been fully elucidated. This study aimed to determine the changes in whole transcriptome in the nucleus of the solitary tract (NTS) in an animal model of PONV, to screen a drug candidate and to elucidate the molecular genetic mechanisms of PONV development. Methods: Twenty‐one female musk shrews were assigned into three groups: the Surgery group (shrew PONV model, n = 9), the Sham group (n = 6), and the Naïve group (n = 6). In behavioral studies, the main outcome was the number of emetic episodes. In genetic experiments, changes in the transcriptome in the NTS were measured. In a separate study, 12 shrews were used to verify the candidate mechanism underlying PONV. Results: A median of six emetic episodes occurred in both the Sham and Surgery groups. Whole‐transcriptome analysis indicated the inhibition of the GABAB receptor‐mediated signaling pathway in the PONV model. Baclofen (GABAB receptor agonist) administration eliminated emetic behaviors in the shrew PONV model. Conclusions: Our findings suggest that the GABAB receptor‐mediated signaling pathway is involved in emesis and that baclofen may be a novel therapeutic or prophylactic agent for PONV. Abstract : Whole‐transcriptome analysis indicated the inhibition of the GABAB receptor‐mediated signaling pathway in the shrew PONV model. After the shrew emetic behaviors, the increase in ADCY1 gene expression, which translates adenyl cyclase (orange), the decrease in GABBR1 gene expression, which translates GABAB receptor R1 subunit (green), and the decrease in CACNB1 gene expression, which translates voltage‐gated calcium channel (blue), were observed. Pharmacological baclofen (GABAB receptor agonist) administration eliminated emetic behaviors in the shrew PONV model.